2021
DOI: 10.3389/fonc.2021.642030
|View full text |Cite
|
Sign up to set email alerts
|

MiR-21-3p Promotes Hepatocellular Carcinoma Progression via SMAD7/YAP1 Regulation

Abstract: BackgroundHepatocellular carcinoma (HCC) remains a major global health burden due to its high prevalence and mortality. Emerging evidence reveals that microRNA (miRNA) plays a vital role in cancer pathogenesis and is widely involved in the regulation of signaling pathways via their targeting of downstream genes. MiR-21-3p, a liver-enriched miRNA, and SMAD7, the negative regulator of the TGF-β signaling pathway, likely exert a vital influence on HCC progression.AimsHere, we explore the role of the miR-21-3p-SMA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 45 publications
1
18
0
Order By: Relevance
“…MiR-21 was also previously reported to regulate pro-oncogenic pathways (MAPK, STAT3, PI3K/AKT, and HiPPO) [ 28 , 55 , 61 , 62 , 63 ], in agreement with our in silico analyses showing that genes upregulated in the absence of miR-21 were involved for example in MAPK, STAT3, and PI3K/AKT signaling ( Figure 1 F and Figure S3 ). We thus investigated the expression and activation by phosphorylation of key effectors of these pro-oncogenic pathways by Western blot.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…MiR-21 was also previously reported to regulate pro-oncogenic pathways (MAPK, STAT3, PI3K/AKT, and HiPPO) [ 28 , 55 , 61 , 62 , 63 ], in agreement with our in silico analyses showing that genes upregulated in the absence of miR-21 were involved for example in MAPK, STAT3, and PI3K/AKT signaling ( Figure 1 F and Figure S3 ). We thus investigated the expression and activation by phosphorylation of key effectors of these pro-oncogenic pathways by Western blot.…”
Section: Resultssupporting
confidence: 91%
“…Finally, genetic deletion of the MiR-21a gene in our miR21KO, LmiR21KO, and LPTENmiR21KO mice also prevents expression of the passenger strand miR-21*, which is not inhibited by antagomiRs against the miR-21-5p. Interestingly, miR-21* (or miR-21-3p) is now reported as a functionally relevant passenger strand, as shown in human HepG2 hepatoblastoma cells where it inhibited growth and triggered apoptosis [ 77 ], but promoted, in another study, migration and invasion of the same cells [ 63 ]. MiR-21* was also reported to play a significant role in other processes such as cardiac and renal fibrosis [ 78 , 79 ], hypertension [ 80 ], or inflammation [ 81 , 82 , 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies identified miR-21-3p target genes: in ovarian cells it targets NAV3 [73], a known tumor suppressor; in hepatocellular carcinoma, it targets SMAD7, an inhibitor of the TGFβ pathway [74]; and in ESCC, it targets TRAF4 [58]. Conversely, miR-21-3p expression upregulates L1CAM, which promotes cell motility, invasion, metastasis, and chemoresistance [75].…”
Section: Plos Onementioning
confidence: 99%
“…Additionally, miR-21 is reported to induce hepatic inflammation through promotion of inflammatory gene expression via the STAT3 signaling pathways, leading to liver disease [38]. High miR-21-3p levels are positively associated with advanced tumor stages [39]. MiR-21-3p promotes metastasis of HCC cells and upregulation of Yes-Associated Protein 1 (YAP1) expression via direct inhibition of SMAD7, which represents a major epigenetic mechanism in the pathogenesis of HCC [39].…”
Section: The Important Roles and Functions Of Micrornas In Hccmentioning
confidence: 99%
“…High miR-21-3p levels are positively associated with advanced tumor stages [39]. MiR-21-3p promotes metastasis of HCC cells and upregulation of Yes-Associated Protein 1 (YAP1) expression via direct inhibition of SMAD7, which represents a major epigenetic mechanism in the pathogenesis of HCC [39]. High-Mobility Group Box 1 (HMGB1) and Cluster Differentiation 44 (CD44) additionally play critical roles in HCC progression.…”
Section: The Important Roles and Functions Of Micrornas In Hccmentioning
confidence: 99%